1999
DOI: 10.1074/jbc.274.30.20749
|View full text |Cite
|
Sign up to set email alerts
|

Base Substitution Specificity of DNA Polymerase β Depends on Interactions in the DNA Minor Groove

Abstract: To examine the hypothesis that interactions between a DNA polymerase and the DNA minor groove are critical for accurate DNA synthesis, we studied the fidelity of DNA polymerase ␤ mutants at residue Arg 283, where arginine, which interacts with the minor groove at the active site, is replaced by alanine or lysine. Alanine substitution, removing minor groove interactions, strongly reduces polymerase selectivity for all single-base mispairs examined. In contrast, the lysine substitution, which retains significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 31 publications
5
64
0
Order By: Relevance
“…The results in Table 1 illustrate that a single amino acid difference not only can reduce replication fidelity but can do so in a highly selective manner, affecting some substitutions but not others. In this regard, the E710A mutant Klenow polymerase is similar to the R283K mutant of DNA polymerase ␤, which has elevated error rates for some mismatches and wild-type rates for others (27). In both instances, these selective influences on error rates are inferred to reflect altered interactions in the binding pocket for the nascent base pair that involve the mutated amino acid side chains and the DNA minor groove.…”
Section: Discussionmentioning
confidence: 97%
“…The results in Table 1 illustrate that a single amino acid difference not only can reduce replication fidelity but can do so in a highly selective manner, affecting some substitutions but not others. In this regard, the E710A mutant Klenow polymerase is similar to the R283K mutant of DNA polymerase ␤, which has elevated error rates for some mismatches and wild-type rates for others (27). In both instances, these selective influences on error rates are inferred to reflect altered interactions in the binding pocket for the nascent base pair that involve the mutated amino acid side chains and the DNA minor groove.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a recently solved ternary complex structure of Sulfolobus solfataricus P2 DNA polymerase (Dpo4), which exhibits a very low fidelity, revealed that the nascent template-primer DNA is in the B-form (42,43). Based on structural and biochemical studies, a common fidelity mechanism involving hydrogen-bonding interactions between the polymerase and the minor groove of the template-primer has been proposed (44,45). An altered conformation of the nascent template-primer can interfere with correct nucleotide incorporation by affecting the geometry of the active site, which interferes with error discrimination by enzymes that scan for correct geometry of the minor groove (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Based on structural and biochemical studies, a common fidelity mechanism involving hydrogen-bonding interactions between the polymerase and the minor groove of the template-primer has been proposed (44,45). An altered conformation of the nascent template-primer can interfere with correct nucleotide incorporation by affecting the geometry of the active site, which interferes with error discrimination by enzymes that scan for correct geometry of the minor groove (45)(46)(47)(48). It has been shown also that the minor groove of the A-form conformation of nascent primertemplate is wider, allowing easy access to the protein side chains and facilitating the interactions of the polymerase and template-primer at the polymerase active site (24,49).…”
Section: Discussionmentioning
confidence: 99%
“…1D). Alanine substitution for this residue dramatically decreases catalytic efficiency and fidelity (16,45,46). Thus, the modest loss of catalytic efficiency (Table 2 and Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%